Tempol improves optic nerve histopathology and ultrastructures in cisplatin-induced optic neuropathy in rats by targeting oxidative stress—Endoplasmic reticulum stress—Autophagy signaling pathways - Alsemeh, Amira Ebrahim; Hulail, Mohey A. E.; Mokhtar, Hanan E. L.; Eldemerdash, Reham Talaat; Banatean-Dunea, Ioan; Fericean, Liana Mihaela; Fathy, Maha Abdelhamid; Arisha, Ahmed Hamed; Khamis, Tarek (Frontiers in Cellular Neuroscience, 2023)
Optic neuropathy is an affection of the optic neurons, it ends with blindness and occurs either primarily due to direct affection of the optic nerve or secondarily as a complication to chronic diseases and/or adverse effect to their therapy. The search for novel therapeutic tools is crucial in addressing the limited therapeutic approaches for optic neuropathy.It is Limited therapeutic approaches emphasize studying new therapeutic tools. Thus, the present study was developed to investigate the possible ameliorative effect of tempol against cisplatin-induced optic neuropathy and its underlying mechanism. Forty-eight adult male albino Wistar rats were divided into 4 equal groups, control, tempol (TEM), cisplatin (CIS), and tempol & cisplatin (TEM+CIS) groups. Optic nerve oxidative stress (MDA, SOD, GPx), gene expression of endoplasmic reticulum stress (ATF-6, XBP-1, BIP, CHOP, JNK), autophagy 6 (LC3, Beclin-1, P62) markers, nerve growth factor-1, immunohistochemical expression of (LC3 & P62), histopathological and electron microscopic examination were performed. Histopathological and ultrastructure examination validated that Cisplatin caused optic neuropathy via induction of oxidative stress, upregulation of ER stress markers, downregulation of autophagy markers, and NGF-1 expression. TEM + CIS showed improvement in optic nerve structure and ultrastructure along with oxidative stress, ER stress mRNA, autophagy (immunohistochemical proteins & mRNA) markers, and nerve growth factor mRNA expression. Based on the previous findings tempol represents a valid aid in cisplatin-induced optic neuropathy via implicating new molecular drug targets (ER stressautophagy) for optic neuropathy therapy.